ANALYSIS OF DIGITAL MARKETING STRATEGY IMPLEMENTATION USING THE SOSTAC MODEL APPROACH AT MAKASSAR STATE UNIVERSITY - Burhanuddin, Burhanuddin; Aswar, Nurul Fadilah; Putra, Muh. Al Fatah Arief (Jurnal Manajemen, 2026)
Abstract: This study analyzes the implementation of Makassar State University's (UNM) digital marketing strategy using the SOSTAC Model approach, which encompasses six strategic elements: Situation, Objectives, Strategy, Tactics, Action, and Control. Using a descriptive qualitative approach and triangulation methods, data were collected through in-depth interviews, observations of UNM's official digital channels, and documentation studies of promotional activities. The results indicate that UNM has an adequate digital infrastructure, but still faces challenges in terms of content relevance, low engagement, and a communication style that is not aligned with the characteristics of Generation Z. A SWOT analysis shows the potential for strengthening the institution's image through digital storytelling, the use of TikTok, and campus community involvement. Strategic recommendations include adopting the 5S framework and the 7P marketing mix, strengthening the KPI-based monitoring system, and establishing a responsive and adaptive digital team. This study emphasizes the importance of structured and data-driven digital marketing planning in improving the competitiveness and positioning of higher education institutions in the era of digital transformation, especially in recruiting prospective students.Keywords: Digital Marketing, SOSTAC, College, Communication Strategy, Generation Z